Tantangan dan Inovasi Dalam Pendidikan Matematika Melalui Pendekatan Multidisiplin Dapat Membangun Keterampilan Berpikir Kritis - Afriana Ritonga, Leli; Sofiyah, Khotnah (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2024)
Mathematics education faces significant challenges in preparing students for an increasingly complex and interconnected world. Traditional approaches are often limited to mastering basic concepts and skills without encouraging essential critical thinking abilities. Therefore, an innovative multidisciplinary approach is needed to improve the quality of mathematics education. This approach integrates concepts from various disciplines, such as science, technology, engineering, and the arts (STEAM), to create a more holistic and relevant learning experience. Students can see connections between concepts, understand real mathematical applications, and develop critical thinking skills through a multidisciplinary approach. This research explores the challenges faced in implementing a multidisciplinary approach in mathematics education and identifies effective innovations to overcome them. The research results show that despite obstacles such as lack of teacher training and resources, a multidisciplinary approach can build students' critical thinking skills, ultimately better preparing them to face future challenges.